The Information Literacy User's Guide An Open, Online Textbook - Bernnard, Deborah; Bobish, Greg; Bullis, Daryl; Hecker, Jenna; Holden, Irina; Hosier, Allison; Jacobson, Trudi; Loney, Tor (Open textbook library., 2014)
Good researchers have a host of tools at their disposal that make navigating today's complex information ecosystem much more manageable. Gaining the knowledge, abilities, and self-reflection necessary to be a good researcher helps not only in academic settings, but is invaluable in any career, and throughout one's life. The Information Literacy User's Guide will start you on this route to success. The Information Literacy User's Guide is based on two current models in information literacy: The 2011 version of The Seven Pillars Model, developed by the Society of College, National and University Libraries in the United Kingdom and the conception of information literacy as a metaliteracy, a model developed by one of this book's authors in conjunction with Thomas Mackey, Dean of the Center for Distance Learning at SUNY Empire State Col- lege.2 These core foundations ensure that the material will be relevant to today's students. The Information Literacy User's Guide introduces students to critical concepts of information literacy as defined for the information-infused and technology-rich environment in which they find themselves. This book helps students examine their roles as information creators and sharers and enables them to more effectively deploy related skills. This textbook includes relatable case studies and scenarios, many hands-on exercises, and interactive quizzes.